Efektivitas E-Modul Dilan Berbasis Android (DIDROID) Terhadap Hasil Belajar IPA Siswa Sekolah Dasar - Naimi, Nadlrah; Azizah, Azizah; Pendit, Sinta Satria Dewi; Zunaedi, Komang Rizki; Isman, Mhd.; Sitepu, Melyani Sari (Jurnal Paedagogy, 2023)
This research aims to analyze the effectiveness of the E-Module Dilan based on Android (DIDROID) on science learning outcomes on heat material on the student’s learning outcomes of class V at SD Inpres Bumi Sagu. This study used experimental research conducted in the experimental and control groups. The research design used was a pretest-posttest control group design. Subjects in this study amounted to 37 students. The instruments used were tests, that was, multiple-choice questions that had been tested for validity and reliability. Data analysis used the prerequisite test, namely the normality and homogeneity tests, and hypothesis testing using the paired sample t-test analyzed using SPSS For Windows 25. Based on the results of this study shows a significance value of 0.000 <0.05 then the hypothesis Ha is accepted, and Ho is rejected, so it can be concluded that the use of the Dilan E-module, based on android (DIDROID) on science learning outcomes on heat material is effectively used on the studentsâ€™ learning outcomes of class V SD Inpres Bumi Sagu.